Investimento em treinamento e seus impactos nos conhecimentos e o retorno financeiro para a empresa: o Caso da Aracruz Celulose S. A. - Nascimento, David Dias do (2003)
The main purpose of this work is to show how the investments in training influence the financial returns of Aracruz Celulose S.A., in the period from january/1998 to december/2000. The data will be treated using quantitative and qualitative parameters. Our analyses will be based on the practical elements. In order to study the idea of investment return in terms of training and questions involving motivation, a knowledge of learning, which is in itself complex because of the varieties of learning theories which don¿t fit into the cultural models being studied, we direct our attention to the necessity of a model which understands the problems of existing conditions. For so much, the most appropriate method for the treatment of data relative to motivation, to knowledge and to learning, will be the ex post facto, because this refers to facts abready known and the researcher would be unable to control or manipulate the variables.